Should we be moving to a national standardized non-gadolinium MR imaging protocol for the surveillance of vestibular schwannomas? - Currie, Stuart (Br J Radiol, 2019)
OBJECTIVES: To examine whether the model of Getting It Right First Time (GIRFT) could be relevant to the surveillance of non-operated vestibular schwannomas (vs) by testing the following hypotheses: (1) in the UK there is a great variation in the imaging protocol for the follow-up of vs; (2) high-resolution, T (2) weighted MRI (HRT (2)W-MRI) has an equivalent accuracy to gadolinium-enhanced T (1) weighted MRI (Gd-MRI) in the assessment of vs size and; (3) imaging with HRT (2)W-MRI rather than Gd-MRI could offer financial savings. METHODS: Two neuroradiologists independently performed measurements of 50 vs imaged with HRT (2)W-MRI and Gd-MRI. Differences in mean tumour measurements between HRT (2)W-MRI and Gd-MRI were determined, as were intra- and interobserver concordance. Level of agreement was measured using Bland–Altman plots. Consultant neuroradiologists within 30 adult neurosurgical units in the UK were contacted via email and asked to provide the MRI protocol used for the surveillance of non-operated vs in their institution. The financial difference between scanning with HRT (2)W-MRI and Gd-MRI was determined within Leeds Teaching Hospitals NHS Trust. RESULTS: There was no statistically significant difference in the mean diameter of vs size, measured on HRT (2)W-MRI and Gd-MRI (p = 0.28 & p = 0.74 for observers 1 and 2 respectively). Inter- and intraobserver concordance were excellent (Interclass correlation coefficient = 0.99, Interclass correlation coefficient ≥ 0.98 respectively). Differences between the two sequences were within limits of agreement. 26 of 30 UK neuroscience centres (87 % response rate) provided imaging protocols. 16 of the 26 (62%) centres use Gd-MRI for the surveillance of vs. HRT (2)-MRI is £36.91 cheaper per patient than Gd-MRI. CONCLUSION: Variation exits across UK centres in the imaging surveillance of non-operated vs. HRT (2)W-MRI and Gd-MRI have equivalent accuracy when measuring vs. Imaging with HRT (2)W-MRI rather than Gd-MRI offers potential financial savings. ADVANCES IN KNOWLEDGE: This study highlights the potential health and economic benefits of a national standardized imaging protocol for the surveillance of non-operated vs.